(untitled) (Annals of Medical Research, 2019)
Aim: This study was planned to determine cut-off values of the Tinetti Performance Oriented Mobility Assessment (POMA) and the Self-Assessment Fall Risk Questionnaire (FRQ) in older adults with mild cognitive impairment. Material and Methods: This study included a total of 213 individuals aged 65 years and over in the study. These individuals were divided into two groups according to Mini Mental Test (MMT) scores: 116 individuals with an MMT score of 18-23 (mild cognitive impairment) and 97 individuals with an MMT score of 24 or more (normal cognitive function). Balance and gait performance was assessed by the POMA, the fall risk self-assessment by older adult susing a FRQ. Results: In Older Adults with mild cognitive function, the clinical cut-off points for the POMA and FRQ were determined according to ROC curve analysis. The clinical cut-off point for the POMA was determined as 15.5 points; and 15.5 points or more in the POMA were considered normal with a 95% confidence level. The clinical cut-off point for the FRQ was determined as 4.5 points; and 4.5 points or less in the FRQ were considered normal with a 95% confidence level. Conclusions: We think that it is important to take the values obtained in the present study into account in interpreting the above-mentioned commonly used tests when cognitive status is considered related to falling. Therefore, it is suggested that these tests used in the clinic should be examined considering the risk of falling in older adults with mild cognitive function.